Effect of fortified calcium compounds from oyster shell on the quality of tapioca pearls - Parinda Meeparn; Chakkapat Aenglong; Savitree Ratanasumawong; Wanwimol Klaypradit; Soraya Kerdpiboon (Food Chemistry, 2024)
This study aimed to determine the effect of calcium fortification from dried oyster shells (DOS) and calcined oyster shells (COS) at concentrations of 2, 4 and 6 %(w/w) on physical and chemical properties of tapioca pearls. The results showed that the optimal cooking time of TP-COS decreased compared to TP-DOS and TP (control). The TP-DOS and TP-COS exhibited a remaining calcium content ranging from 8.39 to 41.03 mg/g. During seven days of refrigerated storage, TP-COS showed delayed hardness along with decreases in both the enthalpy of gelatinization and retrogradation. The functional groups observed in TP-DOS and TP-COS showed varying intensities compared to TP. Morphology images depicted the distribution of DOS and COS within tapioca pearls, revealing that TP-DOS and TP-COS possessed a denser and more compact structure. The results suggest that COS fortification could improve the nutritional value and delay the change in the texture of tapioca pearls after storage.
Keywords: Food composition and properties; Meat and Animal Product Quality; Polysaccharides Composition and Applications